2013
DOI: 10.5660/wts.2013.2.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Various Turf Covers for Kentucky bluegrass Growth and Spring Green-up

Abstract: ABSTRACT. Winter turfgrass injury is one of the critical problems of many golf courses in Korea. Turfgrass loss from freezing injury due to low temperature leads to many types of damages including weed invasion, increased herbicide cost, increased soil erosion, and expensive re-establishment. Although Kentucky bluegrass (Poa pratensis L.) which is the most widely used among cool-season grasses in Korea is well known as cold tolerance species, freezing injuries to Kentucky bluegrass during winter are often foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Non-covered turf had greater turfgrass color than covered turf from May 28 when maximum air temperature reached 30.2 o C (Table 6). Lee (2013) reported similar results with turf cover study. He found non-covered turf had greater -------------------------------------------------Turf quality ------------------------------------------------- ----------------------------------------------- Turf cover was applied at December 7, 2013 immediately after the N treatment.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…Non-covered turf had greater turfgrass color than covered turf from May 28 when maximum air temperature reached 30.2 o C (Table 6). Lee (2013) reported similar results with turf cover study. He found non-covered turf had greater -------------------------------------------------Turf quality ------------------------------------------------- ----------------------------------------------- Turf cover was applied at December 7, 2013 immediately after the N treatment.…”
Section: Resultssupporting
confidence: 80%
“…The air temperature of 30.2 o C measured in the study is the range of optimal temperature for zoysiagrass, but the temperature under cover could be higher than air temperature. Lee (2013) also reported that the temperature difference between air and under cover was 3.1 to 8.7 o C with various types of turf covers. Therefore, the temperature under the cover could be 38.9 o C which is higher than optimal temperature for shoot growth of warm-season grasses.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations